A view from the inside: Integrating the University Library within an Academic Department - Axelsson, Ann-Sofie (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2022)
The library at Chalmers University of Technology in Gothenburg, Sweden is unusual because it is fully integrated within an academic department, the Department of Communication and Learning in Science. This guest editorial explores the opportunities and challenges of integration and offers observation on the learning from establishing this integrated model.